2021
DOI: 10.1098/rsfs.2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal responses to carbon dioxide and light require abscisic acid catabolism in Arabidopsis

Abstract: In plants, stomata control water loss and CO 2 uptake. The aperture and density of stomatal pores, and hence the exchange of gases between the plant and the atmosphere, are controlled by internal factors such as the plant hormone abscisic acid (ABA) and external signals including light and CO 2 . In this study, we examine the importance of ABA catabolism in the stomatal responses to CO 2 and light. By using the ABA 8′-hydroxylase-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…However, there is disagreement as to the precise role of ABA in stomatal responses to CO 2 , as other studies suggest that ABA and ABA signalling are required for elevated CO 2 induced stomatal closure 38 . Most recently, a study has shown ABA catabolism plays a role in regulating stomatal responses to changes in CO 2 concentration both on a physiological and developmental scale 39 . A set of control leaf discs were kept in the dark for 120 min over the same period (120 min D).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is disagreement as to the precise role of ABA in stomatal responses to CO 2 , as other studies suggest that ABA and ABA signalling are required for elevated CO 2 induced stomatal closure 38 . Most recently, a study has shown ABA catabolism plays a role in regulating stomatal responses to changes in CO 2 concentration both on a physiological and developmental scale 39 . A set of control leaf discs were kept in the dark for 120 min over the same period (120 min D).…”
Section: Discussionmentioning
confidence: 99%
“…ABA is an essential hormone regulating plants tolerant to abiotic and biotic stress ( Lee and Luan, 2012 ; Danquah et al, 2014 ). It is well known that ABA induces the closure of stoma to reduce evaporation ( Hsu et al, 2021 ; Movahedi et al, 2021 ). Hence in the GO analysis at ABA treatment, the module contained genes responding to heat and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Light has also been suggested to regulate ABA biosynthesis directly or indirectly [68], however, the literature data on the light-induced changes in ABA content are contradictory [69][70][71][72]. Earlier findings suggested a positive feedback loop between ABA and PAs [61,73].…”
Section: Effect Of Light Quantity On Salicylic Acid and Abscisic Acid Synthesis And Its Relation To Pa Metabolismmentioning
confidence: 99%